2015
DOI: 10.1021/acsami.5b01963
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Step Synthesis of Three-Dimensional Pd–Ag Bimetallic Alloy Networks and Their Electrocatalytic Activity toward Ethanol Oxidation

Abstract: The three-dimensional palladium networks and palladium-silver bimetallic alloy networks were synthesized at room temperature on a large scale using a rapid and simple strategy. The results revealed that the morphology of the networks is not affected by the composition. We demonstrated that the as-prepared unsupported networks exhibited excellent electrochemical activity and stability toward ethanol oxidation reaction in alkaline media due to the formation of palladium-silver alloys as well as the porous nanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 46 publications
13
106
0
Order By: Relevance
“…Two components alloying of Pd with other metals have been intensively studied, while the multi-alloying still needs to be put more attention, and the muli-alloying also provides vast variations in the choice and combination of different metals. Novel nanostructure of Pd is still a popular topic in this field [136][137][138][139][140][141]. …”
Section: Pd-based Catalysts For the Direct Ethanol Fuel Cells (Defcs)mentioning
confidence: 99%
“…Two components alloying of Pd with other metals have been intensively studied, while the multi-alloying still needs to be put more attention, and the muli-alloying also provides vast variations in the choice and combination of different metals. Novel nanostructure of Pd is still a popular topic in this field [136][137][138][139][140][141]. …”
Section: Pd-based Catalysts For the Direct Ethanol Fuel Cells (Defcs)mentioning
confidence: 99%
“…It has been reported that modifications of the Pd nanocatalyst by metals such as Ni [6][7][8], Au [9,10], Cu [10,11], Ag [10,12], Co [10,13 ] effectively improve the catalytic performances of the Pd nanocatalyst toward alcohol oxidations in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…10.1%), together with up to 80.2% of the concentration of Ag(I) --species in the Ag@Pd/C-2, again indicating that electrons can transfer from Ag atoms to Pd atoms, thus leading to a strong interaction between Ag and Pd. [38] The mass specific activity (MSA) was evaluated by using the current density at the potential of 0.345 V as shown in Table 2. [32] Figure 4 compares the cyclic voltammograms (CVs) of three Ag@Pd/C nanoparticles, Pd/C, and commercial Pd black catalyst.…”
Section: Resultsmentioning
confidence: 99%